2022
DOI: 10.1590/1806-9061-2022-1633
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Equations of Carcass Characteristics and Primal Cut Weights of Native Mexican Guajolotes Using Body Measurements

Abstract: This study was conducted to develop predictive equations for carcass characteristics and primal cut weights of native Mexican guajolotes using body measurements (BM). For this study, a total of 36 male guajolotes (Meleagris gallopavogallopavo), aged 6 to 10 months, and mean slaughter body weight (SBW) of 4543.14 ± 656.60 g, were used. The birds were kept under traditional extensive conditions. ThefollowingBMswererecorded24 h before slaughter: thoracicperimeter (TP), body circumference (BC), body length (BL), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In this way, the results obtained in this study suggest that cold carcass weight showed a greater discriminant capacity than slaughter weight. Portillo-Salgado et al [130] claimed that slaughter weight explained by itself 95% of the variation in cold canal weight. However, differences across breeds could arise when facing the post-slaughter cooling process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the results obtained in this study suggest that cold carcass weight showed a greater discriminant capacity than slaughter weight. Portillo-Salgado et al [130] claimed that slaughter weight explained by itself 95% of the variation in cold canal weight. However, differences across breeds could arise when facing the post-slaughter cooling process.…”
Section: Discussionmentioning
confidence: 99%
“…Carcass components grow in parallel with live weight as the animal ages [127,129]. How-ever, selection for greater development of certain body parts [130] and in premature stages of life [140] has been performed. This is due to the great value of and demand for primary cuts in the market [129].…”
Section: Discussionmentioning
confidence: 99%